PENDIDIKAN KRITIS DALAM PANDANGAN MANSOUR FAKIH - Muhammad Ramadhansyah; Mohamad Ali (Universitas Muhammadiyah Surakarta, 2019)
This research examines the theory of critical education in the view of Mansour Fakih. By proposing the problem formulations: What is Mansour Fakih’s view of critical education theory and how are Mansour Fakih’s critical education practices. This study is categorized as library research, where all the activities of this study are focused on the reviews of books and literature that correlate with the subject of this study. This study uses Hermeneutic Philosophy that interprets as objective as possible of a symbol in the form of text to find the correct understanding, and this study also uses philosophy to define logically and freely. This study uses a descriptive analysis method to analyze as carefully as possible of related data about the idea of critical education of Mansour Fakih through the description of its point holistically. Then it will be analyzed and interpreted based on the thought of the figures studied. The result of this study is the ideal theory of critical education that expect awareness from human, as active actors that aware of their own life as well as critical view Mansour Fakih about the purpose of education that is critical reflection toward an unfair applied system and critical education practices that which consist of 5 stages, they are started by doing, then reveal the data, study, conclude, and the last one is action or implementation.